Effect of FOMO and Hedonic Value on Impulsive Buying and Post Purchase Regret for Purchasing Skincare Products at the Online Shop - Euis Nurmalasari; Iin Hartini; Raissa Ariany Putri; Primidya Kartika Miranda Soesilo (Management Institute Faculty of Economics Universitas Andalas, 2024)
Skincare products have become an important part of Indonesian women's routine. With the development of social media, impulse buying is on the rise, often driven by fear of missing out from trends (FoMO) and hedonic values. This study aims to analyze the effect of FoMO and Hedonic Value's effect on impulsive purchases and post-purchase regret. Using multiple regression analysis with Smart PLS, our findings indicate significant effects of FoMO and Hedonic Value on impulsive buying, which in turn significantly affects post-purchase regret. Data for this study were collected through an online questionnaire distributed via Google Forms, targeting women aged 24-39 in Greater Jakarta. The questionnaire consisted of 22 items divided into four sections derived from previous studies. A total of 220 responses were analyzed to ensure the robustness of the results. This study found that FoMO and hedonic values have significant effect on impulsive buying. Then, impulsive buying has significant effect on post-purchase regret. This study contributes to understanding how psychological factors influence consumer behavior in the digital shopping landscape.